2020
DOI: 10.1113/jp279483
|View full text |Cite
|
Sign up to set email alerts
|

Spike‐wave discharges in absence epilepsy: segregation of electrographic components reveals distinct pathways of seizure activity

Abstract: Key points The major electrophysiological hallmarks of absence seizures are spike and wave discharges (SWDs), consisting of a sharp spike component and a slow wave component. In a widely accepted scheme, these components are functionally coupled and reflect an iterative progression of neuronal excitation during the spike and post‐excitatory silence during the wave. In a genetic rat model of absence epilepsy, local pharmacological inhibition of the centromedian thalamus (CM) selectively suppressed the spike co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 66 publications
0
28
1
Order By: Relevance
“…In this issue of The Journal of Physiology , Terlau et al . (2020) (and many references therein) confirmed the Yin and Yang of SWDs in the GAERS model as recorded with silicon probes by showing increased multi‐unit activity during the spike of the spike‐wave complex at the site of origin, the facial area of the somatosensory cortex (S1), followed by neuronal silence. Moreover, they identified both cortical layer specific sinks during the spike and sources during the wave, illustrating that interlaminar processes in all cortical layers play a role in the occurrence of SWDs.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…In this issue of The Journal of Physiology , Terlau et al . (2020) (and many references therein) confirmed the Yin and Yang of SWDs in the GAERS model as recorded with silicon probes by showing increased multi‐unit activity during the spike of the spike‐wave complex at the site of origin, the facial area of the somatosensory cortex (S1), followed by neuronal silence. Moreover, they identified both cortical layer specific sinks during the spike and sources during the wave, illustrating that interlaminar processes in all cortical layers play a role in the occurrence of SWDs.…”
mentioning
confidence: 60%
“…This results as described by Terlau et al . (2020) are important and interesting for several reasons. The fact that the wave remained untouched and that the spike vanished shows an obvious dissociation between the spike and the wave, and this has never been so clearly experimentally demonstrated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our model does not differ between GABA(A) and GABA(B) currents (the model of an individual node is not detailed enough for this), therefore our model cannot be used to investigate the contribution of these conductances which could play a role in the difference in frequency between rodents and people. Many different cortical cell layers interact differently during spike and waves as was established in GAERS [ 73 ], others showed preictal intracortical processes in WAG/Rij rats [ 74 ]. Future models might indeed require different populations of cells in different cortical layers, also since it was found that the superficial layers of the somatosensory cortex are indispensable for the occurrence of SWDs, while the deeper layers communicate directly with the thalamus [ 75 ].…”
Section: Discussionmentioning
confidence: 99%